The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1088/0953-8984/13/14/312
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of Coulomb drag between ballistic quantum wires

Abstract: The Coulomb drag between two spatially separated one-dimensional (1D) electron systems in lithographically fabricated 2 µm long quantum wires is studied experimentally. The drag voltage V D shows peaks as a function of a gate voltage which shifts the position of the Fermi level relative to the 1D subbands. The maximum in V D and the drag resistance R D occurs when the 1D subbands of the wires are aligned and the Fermi wave vector is small. The drag resistance is found to decrease exponentially with interwire s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
93
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 34 publications
(38 reference statements)
5
93
0
3
Order By: Relevance
“…In contrast to the noise, the absolute drag of the current is not based on a symmetry of the Hamiltonian and is therefore restricted to asymptotically small energy scales k B T, eU and a large contact region between the tubes. Recently, current drag effects have been observed for crossed SWNTs [20] and parallel semiconductor quantum wires [21]. Essentially the same systems should also reveal the Coulomb drag shot noise predicted here.…”
supporting
confidence: 73%
“…In contrast to the noise, the absolute drag of the current is not based on a symmetry of the Hamiltonian and is therefore restricted to asymptotically small energy scales k B T, eU and a large contact region between the tubes. Recently, current drag effects have been observed for crossed SWNTs [20] and parallel semiconductor quantum wires [21]. Essentially the same systems should also reveal the Coulomb drag shot noise predicted here.…”
supporting
confidence: 73%
“…They have been used to investigate properties of electron-electron scattering in low-density 2D electron systems Kellogg et al, 2002a); signatures of metal-insulator transition in dilute 2D hole systems (Jörger et al, 2000a,b;Pillarisetty et al, 2002Pillarisetty et al, , 2005a; quantum coherence of electrons (Kim et al, 2011;Price et al, 2008Price et al, , 2007 and composite fermions (Price et al, 2010); exciton effects in electron-hole bilayers Keogh et al, 2005;Morath et al, 2009;Seamons et al, 2009); exotic bilayer collective states (Eisenstein, 2014), especially the quantum Hall effect (QHE) at the total filling factor ν T = 1 (Finck et al, 2010;Kellogg et al, 2003Kellogg et al, , 2002bSchmult et al, 2010;Spielman et al, 2004;Tutuc et al, 2009); compressible quantum Hall (QH) states at half-integer filling factor (Muraki et al, 2004;Zelakiewicz et al, 2000); integer QH regime (Lok et al, 2002); Luttinger liquid effects (Debray et al, 2001;Laroche et al, 2008Laroche et al, , 2014; Wigner crystallization in quantum wires (Yamamoto et al, 2002(Yamamoto et al, , 2006(Yamamoto et al, , 2012; and one-dimensional (1D) sub-bands in quasi 1D wires (Debray et al, 2000;Laroche et al, 2011). More generally, interlayer interaction and corresponding transport properties have been studied in hybrid devices comprising a quantum wire and a quantum dot (Krishnaswamy et al, 1999); a SC film and a 2D electron gas (Farina et al, 2004); Si metal-oxide-semiconductor systems …”
Section: Frictional Dragmentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.117.066602 Coulomb-coupled quantum dots yield a model system for Coulomb drag [1], the phenomenon where a current flowing in a so-called drive conductor induces a voltage across a nearby drag conductor via the Coulomb interaction [2]. Though charge carriers being dragged along is an evocative image, as presented in early work on coupled 2D-3D [3] or 2D-2D [4] semiconductor systems, later measurements in graphene [5,6], quantum wires in semiconductor 2DEGs [7][8][9][10], and coupled double quantum dots [11] have indicated that the microscopic mechanisms leading to Coulomb drag can vary widely. For example, collective effects are important in 1D, but less so in other dimensions.…”
mentioning
confidence: 99%